COMPARATIVE OSTEOLOGY OF THE FISHES OF THE FAMILY LEIOGNATHIDAE PART II: RELATIONSHIPS AMONG THE GENERA AND THE SPECIES - James, P S B R (Indian Journal of Fisheries, 2011)
While the three genera, Leiognathus, Secutor and Gazza, in the family Leiognathidae share some osteological characters in common, they differ from one another strikingly in certain characters (Table 2). The differences between the genera appear to be more pronounced in the otic region of the skull than elsewhere. The differences between Leiognathus and Secutor, between Leiognathus and Gazza and between Secutor and Gazza are shown in Tables 3 to 5 respectively. The study indicates that osteologically the genus Leiognathus is more distantly related to Secutor than Leiognathus to Gazza or Secutor to Gazza